1997
DOI: 10.1155/1997/839686
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Malignancy Associated Changes in Cervical Cell Nuclei Using Feed‐Forward Neural Networks

Abstract: Normal cells in the presence of a precancerous lesion undergo subtle changes of their DNA distribution when observed by visible microscopy. These changes have been termed Malignancy Associated Changes (MACs). Using statistical models such as neural networks and discriminant functions it is possible to design classifiers that can separate these objects from truly normal cells. The correct classification rate using feed‐forward neural networks is compared to linear discriminant analysis when applied to detecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…High-level image interpretation has been used in a wide range of applications [Hudson and Cohen, 2000;Duda et al, 2001] including microscope images of: cervical smears [Kemp et al, 1997;Mackin et al, 1998;Van der Laak et al, 2002]; premalignant prostate, colon and esophageal tissue [Weyn et al, 2000]; and cultured cells [Boland et al, 1998;Boland and Murphy, 2001]. However, automated image interpretation using classical clinical stains (e.g., hematoxylin and eosin, and variations of the Pap stain) has only shown limited success [Bartels and Vooijs, 1999].…”
Section: Prospecting For New Cytodiagnostics By Imaging Molecular Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-level image interpretation has been used in a wide range of applications [Hudson and Cohen, 2000;Duda et al, 2001] including microscope images of: cervical smears [Kemp et al, 1997;Mackin et al, 1998;Van der Laak et al, 2002]; premalignant prostate, colon and esophageal tissue [Weyn et al, 2000]; and cultured cells [Boland et al, 1998;Boland and Murphy, 2001]. However, automated image interpretation using classical clinical stains (e.g., hematoxylin and eosin, and variations of the Pap stain) has only shown limited success [Bartels and Vooijs, 1999].…”
Section: Prospecting For New Cytodiagnostics By Imaging Molecular Labelsmentioning
confidence: 99%
“…This suggests similarity in odd shapes occurring both in 'doublets' and in 'mitotic cells. ' The resulting performances of the automated high-level image interpreters can vary widely (anywhere between 60 and 100%) depending on how similar the object classes are, how discriminating the molecular biomarker(s) used for imaging is (are), and whether the differences in the imaged objects are simple on-off decisions, like for rare event detection of fetal nucleated red blood cells in maternal peripheral blood [Bianchi, 1999;Bajaj et al, 2000;Bianchi et al, 2002;Yamanishi et al, 2002], images of which are shown in Figure 7 (left), or fine differences, e.g., in texture of the molecular marker that can classify cells with malignancy associated changes [Kemp et al, 1997]. An example of a breast cancer specific marker, anti-cytokeratin- Fig.…”
Section: Prospecting For New Cytodiagnostics By Imaging Molecular Labelsmentioning
confidence: 99%
“…An artificial neural network (ANN) is inspired by the manner of biological nervous system, such as human brain to process the data, and is one of the numerous algorithms used in machine learning and data mining (Dasarthy, 1990; Kemp et al, 1997; Goebel & Gruenwald, 1999; Hegland, 2003; Kantardzic, 2011). In a feedforward neural network (FFNN), data processing has only one forward direction from the input layer to the output layer without any backward loop or feedback connection (Bose & Liang, 1996; McCloskey, 2000; Andonie & Kovalerchuk, 2007; Kantardzic, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It takes years for an abnormal cell to grow, and we need the earliest possible sign of abnormality to let for the earliest treatment [1][2][3]. ThinPrep Pap smear screening can be useful as an early diagnostic process which can diagnose the cervical cancer [4,5]. Finding abnormal cells in ThinPrep Pap smears is an error-prone and difficult problem for pathologists.…”
Section: Introductionmentioning
confidence: 99%